CLINICAL APPLICATION OF NIGHTINGALE’S THEORY INTO PRACTICE - yasmeen, samina; Iqbal, Javed; Hazara, Shair Mohammad; Akhtar, Nourin (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Nurses are the backbone of any healthcare system. However, nurses are still struggling with many challenges particularly in the developing world. One of the biggest challenge of today’s nurse is the clinical application of nursing theoretical concepts into routine practice. The purpose of this scholarly paper is to explicitly describe the Nightingale nursing theory into clinical practice in light of a clinical scenario particularly three core concepts (Bed and bedding, proper ventilation of ward, and proper hygienic dressing) in order to demonstration the evidence based practice in nursing care